Literature Review on the Effectiveness of the Flipped Classroom in Enchancing Students’ Academic Achievement in Indonesia - Darobi, Muhammad; Harini, Harini; Noviani, Leny (Jurnal Pendidikan Progresif, 2023)
Literature Review on the Effectiveness of the Flipped Classroom learning Model in Enchancing Students’ Academic Achievement This study discusses the effectiveness of the Flipped Classroom instructional model in enhancing academic achievement based on a literature review. This learning model is an innovation that transforms the conventional teaching paradigm by utilizing information technology. The research aims to explore the impact of implementing the Flipped Classroom model on improving learning outcomes in Economics by presenting a comprehensive literature review on the use of the Flipped Classroom model in the context of economic education. The research method employed is a Systematic Literature Review (SLR) from various sources, where the author explores various related studies to determine whether the Flipped Classroom model consistently improves students' academic performance in an educational context. The literature review results indicate that the Flipped Classroom has the potential to enhance students' academic achievements. Some studies show a significant improvement in conceptual understanding, learning motivation, and active student participation when this model is well implemented. However, there are also findings highlighting challenges in implementing the Flipped Classroom, such as adequate material preparation, teacher roles, and technology access. Keywords: flipped classroom, academic achievement, learning model, students, economics learning.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202330